Estimating the Direct Cost of Cancer in Nepal: A Cross-Sectional Study in a Tertiary Cancer Hospital - Khatiwoda, Shiva Ram; Dhungana, Raja Ram; Sapkota, Vishnu Prasad; Singh, Sarswoti (Frontiers in Public Health, 2019)
Background: Increasing prevalence of cancer and lack of strong health financing system in least income countries like Nepal is exerting enormous financial burden to the cancer patient. However, there is scant information relating to the amount of expenditure in utilizing health services for cancer in Nepal. Therefore, this study aimed to estimate the direct cost associated with treatment of cancer among the patients attending a tertiary cancer treatment center in Nepal. Methods: A quantitative cross-sectional study was carried out among 294 cancer patients who were receiving treatment from Bhaktapur Cancer Hospital between 17th November 2016 and 13th February 2017. Direct medical cost and non-medical costs borne by the patients were calculated based on the cost of illness methodology. Medical cost included the cost of consultation, diagnosis and treatment while non-medical cost comprised the cost occurred out of health facility such as cost of food, travel and accommodations. Result: Of those 294, 169 (57.5%) were female and 125 (42.5%) were male. The median (IQR) age was 54 (19) years. Cancer of the lung was present in 19.39%, breast in 15.65% and cervix in 14.29%. Mean (SD) and Median (IQR) direct cost of cancer was NRs 387.5 (196.8) and 346.1 (260.5) thousands. Medical cost contributed to 80.91% of the total direct cost. Almost everyone relied on out-of-pocket (OOP) payment for cancer treatment where 253 (86.1%) participants reported that they were experiencing financial hardship, 230 (78.2%) took a loan and 140 (47.6%) sold their property to manage the OOP. Both medical and non-medical costs were significantly varied with age, socio-economic status, types of cancer and the treatment. Conclusion: Medical cost contributed most to the direct cost. OOP was dominant payment mechanism to utilize health services. Average direct cost of cancer was higher than the average income of the people, sufficient to cause financial catastrophe. This implies the need of improved health financing strategy to protect people from financial hazards of health service utilization for cancer in Nepal.